PENGARUH STIMULASI TERHADAP PERKEMBANGAN ANAK SEBAGAI TINDAK LANJUT DDTKA MASAL PASCA PENCATATAN REKOR MURI DI KOTA BLITAR - Martiningsih, Wiwin; Setijaningsih, Triana; Winarni, Sri (University of Muhammadiyah Malang, 2012)
Children must get serious attention in early of their life such as good nutrition, appropriate stimulation, good environment factors, early detection and intervention of development delays. The development is the increasing of the skill in structure and function of body in more complex and in regular pattern and predictable, as result of maturation process. The research’s purpose is to know the influence of stimulation to child’s development after DDTKA massal in Blitar city. The research type is quasy experiment, and the sample is children that have hesitate and delay developments after DDTKA massal in Blitar city, with inclution criteria: has normal growth, visit to posyandu regularly in the latest 3 mounts and have good health, there are 20 children. The sampling technique uses purposive sampling. The independent variable is stimulation of development, and the dependent variable is development of child. Data is collected using observation sheet and questioner of KPSP. The analysis use wilcoxson signed ranks test, statistic test with sensing level p < 0,05. We can get result as follows: 1) development of child before giving stimulation is 70% hesitate, 30% have delay, after stimulation is normal (65%), 25% hesitate and 10% have delay; 2) there is influence of stimulation to child development (p-value 0,000). We can conclude that the care pattern to child in their family to achieve optimal developments is important.